PaleoView: a tool for generating continuous climate projections spanning the last 21 000 years at regional and global scales. Issue 11 (12th May 2017) - Fordham, Damien A.; Saltré, Frédérik; Haythorne, Sean; Wigley, Tom M. L.; Otto‐Bliesner, Bette L.; Chan, Ka Ching; Brook, Barry W.
Abstract : It has been difficult to access projections of global‐scale climate change with high temporal resolution spaning the late Pleistocene and Holocene. This has limited our ability to discern how climate fluctuations have affected species' range dynamics and extinction processes, turn‐over in ecological communities and changes in genetic diversity. PaleoView is a new freeware tool, which provides a comprehensive but easy‐to‐use way to generate and view paleoclimate data at temporal and spatial resolutions suitable for detecting biotic responses to major climate shifts since the last glacial maximum. Regional to global scale simulations of temperature, precipitation, humidity and mean sea level pressure can be generated from PaleoView as gridded or time series data at time intervals as short as a decade for any period during the last 21 000 yr. They can be viewed using a built‐in geographical user interface or saved as data files. Modelled climate reconstructions are based on daily simulation output from the Community Climate System Model ver. 3 (CCSM3). This global coupled atmosphere–ocean–sea ice–land general circulation model accurately reproduces major climatic features associated with the most recent deglaciation event, and predicts present‐day patterns of climate conditions with verified hindcast skill. By providing a portal for readily accessing climate reconstructions at high temporal resolutions, PaleoView can help to better establish the consequences of past climate fluctuations on macro‐ecological patterns of biological and genetic diversity.